Integrated transcriptomic and metabolomic analyses identify key factors in the vitellogenesis of juvenile Sichuan bream (Sinibrama taeniatus) - Zhao, Zhe; Zhao, Qiang; Wang, Haoyu; Wei, Lan; Wang, Siya; Li, Shilin; Yuan, Dengyue; Wang, Zhijian (Frontiers in Marine Science, 2023)
Vitellogenesis is the most important stage of ovarian maturation in fish, involving the synthesis and transport of essential yolk substances and their complex mechanisms and coordination process. The liver is the main tissue involved in the vitellogenesis of oviparous animals, but studies of vitellogenesis in fish rarely include the liver and ovary as a whole. The aim of this study was to explore the molecular mechanism and associated regulatory factors behind vitellogenesis in Sichuan bream (Sinibrama taeniatus). The different stages of oogenesis were first identified by successive histological observations. Then, ovary and liver tissues that developed to 115 days (stage II, previtellogenesis stage), 165 days (stage III, vitellogenesis stage) and 185 days (stage IV, late-vitellogenesis stage) were collected for transcriptomic and metabolomic analyses, and serum testosterone (T), 17β-estradiol (E2), vitellogenin (Vtg), triiodothyronine (T3), and thyroxine (T4) levels were measured at the corresponding stages. We found that energy redistribution during vitellogenesis is mainly regulated through glycolysis, fatty acid biosynthesis and the citrate cycle pathway. In the liver, energy metabolism was promoted by activating glucolipid metabolic pathways to provide sufficient ATP, but at the same time, the ovary tends to retain nutrients rather than decompose them to produce energy. In addition, we have identified several key factors involved in the metabolism of neutral lipids, polar lipids, amino acids and vitamins, which are involved in the assembly and transport of important yolk nutrients. The initiation of vitellogenesis was found to be associated with a surge in serum E2 levels, but the sustained increase in Vtg levels in the late stage may be due more to upregulation of the estrogen receptor. These results provide valuable information about the regulation of ovarian development in cultured fish.